2011
DOI: 10.1073/pnas.1010396108
|View full text |Cite
|
Sign up to set email alerts
|

Contractility of the cell rear drives invasion of breast tumor cells in 3D Matrigel

Abstract: Cancer cells use different modes of migration, including integrindependent mesenchymal migration of elongated cells along elements of the 3D matrix as opposed to low-adhesion-, contractionbased amoeboid motility of rounded cells. We report that MDA-MB-231 human breast adenocarcinoma cells invade 3D Matrigel with a characteristic rounded morphology and with F-actin and myosin-IIa accumulating at the cell rear in a uropod-like structure. MDA-MB-231 cells display neither lamellipodia nor bleb extensions at the le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

23
260
3

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 255 publications
(292 citation statements)
references
References 39 publications
23
260
3
Order By: Relevance
“…5,31 The migration speed of human foreskin fibroblasts in cell-derived 3D matrices and human breast adenocarcinoma cells in 3D Matrigel were reduced following blebbistatin treatment. 5,31 Our studies were performed with HT1080 cells migrating in 3D collagen I matrices, whereas the previous experiments were done with other cell types migrating in 3D cell-derived matrices or 3D Matrigel. Therefore, the differences in matrices as well as cell types could contribute to the differential effect observed on migration with blebbistatin treatment.…”
Section: Asef2 Promotes S19 Phosphorylation Of Myoii Through Racmentioning
confidence: 99%
“…5,31 The migration speed of human foreskin fibroblasts in cell-derived 3D matrices and human breast adenocarcinoma cells in 3D Matrigel were reduced following blebbistatin treatment. 5,31 Our studies were performed with HT1080 cells migrating in 3D collagen I matrices, whereas the previous experiments were done with other cell types migrating in 3D cell-derived matrices or 3D Matrigel. Therefore, the differences in matrices as well as cell types could contribute to the differential effect observed on migration with blebbistatin treatment.…”
Section: Asef2 Promotes S19 Phosphorylation Of Myoii Through Racmentioning
confidence: 99%
“…Moreover, ZBP1 is broadly expressed in non-metastatic breast cell lines and human tumors, but is downregulated in metastatic cells (Gu et al, 2009). A recent study reported that human metastatic MDA231 cells, which do not express IMP1/ZBP1, display neither lamellipodia nor bleb extensions at the leading edge and invade 3D Matrigel with a characteristic rounded morphology using a uropod-like structure (Poincloix et al, 2011). It is suggested that cells that are able to localize b-actin mRNA retain a stable and persistent polarity, leading to reduced responsiveness to orient towards exogenous chemotactic gradients; such responsiveness is required for cellular invasiveness and hence reduced metastatic potential (Lapidus et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…One such strategy involves the actuation of nonmuscle cell contractility to drive a wide range of developmental processes as well as normal physiological and pathological disease states (1-5). The contractile behaviors of cells and their interactions in multicellular arrays are not only critical in shaping and guiding tissue formation (e.g., epithelial folding) for the successful outcome of development programs (6, 7), but also play a major role in the pathology of tumor growth, the invasionmetastasis cascade, wound healing, and tissue regeneration (8,9).…”
mentioning
confidence: 99%
“…One such strategy involves the actuation of nonmuscle cell contractility to drive a wide range of developmental processes as well as normal physiological and pathological disease states (1-5). The contractile behaviors of cells and their interactions in multicellular arrays are not only critical in shaping and guiding tissue formation (e.g., epithelial folding) for the successful outcome of development programs (6, 7), but also play a major role in the pathology of tumor growth, the invasionmetastasis cascade, wound healing, and tissue regeneration (8,9).From a signaling standpoint, embryonic development is a dynamic process where cells interact and coordinate force generation as their identities are patterned by spatiotemporally applied chemical stimuli. There has been considerable debate over the effectiveness of intra-versus intercellular signaling during development (10, 11); nevertheless, the cell-cell signaling and the coordination of a variety of multicellular responses are known to be mediated by gap-junction-dependent intercellular communication (12, 13).…”
mentioning
confidence: 99%